Machine Learning in Fraud Detection for Financial Services in Real time Data - Praveen Kumar Rawat (PT. Delitekno Media Mandiri, 2026)
Fraud detection has become a critical concern for financial institutions seeking to safeguard their assets and maintain client trust in an increasingly digitized financial landscape. This study examines the application of machine learning (ML) techniques to enhance fraud detection systems within financial institutions. By leveraging computational algorithms and data analytics, organizations can identify patterns and anomalies in transaction data that conventional rule-based approaches often fail to detect. The efficacy of multiple ML paradigms, including supervised, unsupervised, and reinforcement learning, in identifying fraudulent activities is evaluated through a systematic review of existing literature and comparative analysis of model performance across benchmark datasets. The study highlights the critical role of feature engineering and data preprocessing in building robust ML models, as the quality of input data significantly influences predictive accuracy. The integration of real-time data processing, which enables organizations to respond to emerging threats promptly, is also examined. Key challenges are discussed, including high false positive rates, class imbalance inherent in fraud datasets, and the necessity for continuous model adaptation to track evolving fraud patterns. The findings indicate that ML-based approaches not only improve fraud detection rates but also enhance operational efficiency and customer satisfaction. This paper serves as a foundational reference for practitioners and researchers aiming to advance the application of machine learning for fraud detection in the financial sector.